Antibacterial potential of a novel Lactobacillus casei strain isolated from Chinese northeast sauerkraut and the antibiofilm activity of its exopolysaccharides. Issue 5 (14th May 2020) - Xu, Xiaoqing; Peng, Qing; Zhang, Yuwei; Tian, Dandan; Zhang, Pengbo; Huang, Ying; Ma, Lan; Dia, Vermont P.; Qiao, Yu; Shi, Bo
Abstract : Exopolysaccharide-producing Lactobacillus spp. isolated from sauerkraut, as probiotics, have shown efficacy in the inhibition of pathogenic bacteria in the intestinal tract. Abstract : Lactobacillus spp., as probiotics, have shown efficacy in the inhibition of pathogenic bacteria in the intestinal tract. In this study, we investigated the antibacterial activity of Lactobacillus casei NA-2, which was isolated from northeast sauerkraut in China. The results of co-culture suggested that L. casei NA-2 could inhibit the growth of Bacillus cereus, Staphylococcus aureus, Salmonella typhimurium and Escherichia coli O157:H7. Moreover, L. casei NA-2 could adhere to the four pathogenic bacteria potentially associated with its exopolysaccharide (EPS). EPS from L. casei NA-2 was then isolated and its activity determined. The results showed that EPS inhibited the biofilms of B. cereus, S. aureus, S. typhimurium and E. coli O157:H7, with the highest inhibition ratios of 95.5% ± 0.1%, 30.2% ± 3.3%, 14.3% ± 0.6%, and 16.9% ± 5.4%, respectively. Moreover, EPS was able to disperse B. cereus, S. aureus, S. typhimurium and E. coli O157:H7 by 94.1% ± 1.2%, 31.8% ± 8.6%, 40.8% ± 3.3% and 49.6% ± 3.8%, respectively. Results showed that EPS from L. casei NA-2 have potential antibacterial properties by inhibiting biofilm formation and dispersing pathogenic bacteria. In conclusion, the antibiofilm property of the EPS on the surface of L. casei NA-2 is one of the possible reasons for antibacterial activity of L. casei NA-2.